2022
DOI: 10.3389/fphar.2022.953871
|View full text |Cite
|
Sign up to set email alerts
|

Integrative network pharmacology and experimental verification to reveal the anti-inflammatory mechanism of ginsenoside Rh4

Abstract: Inflammation is an innate immune response to infection, and it is the main factor causing bodily injury and other complications in the pathological process. Ginsenoside Rh4 (G-Rh4), a minor ginsenoside of Panax ginseng C. A. Meyer and Panax notoginseng, has excellent pharmacological properties. However, many of its major pharmacological mechanisms, including anti-inflammatory actions, remain unrevealed. In this study, network pharmacology and an experimental approach were employed to elucidate the drug target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…At the same time, studies on ginsenoside rh4 have also demonstrated its significant anti-inflammatory activity. Hu et al found through RT-PCR, Western blot, and ELISA analyses that ginsenoside rh4 significantly inhibited the production of pro-inflammatory cytokines (such as TNF-α, IL-6, and IL-1β) and inflammation-related enzymes induced by lipopolysaccharide (LPS) 38 . Additionally, ginsenoside rh4 can interfere with NFIL3, inhibiting myocardial remodeling induced by Ang II 39 .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, studies on ginsenoside rh4 have also demonstrated its significant anti-inflammatory activity. Hu et al found through RT-PCR, Western blot, and ELISA analyses that ginsenoside rh4 significantly inhibited the production of pro-inflammatory cytokines (such as TNF-α, IL-6, and IL-1β) and inflammation-related enzymes induced by lipopolysaccharide (LPS) 38 . Additionally, ginsenoside rh4 can interfere with NFIL3, inhibiting myocardial remodeling induced by Ang II 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, Rh4 can exert antiinflammatory effects by regulating the NF-κB and STAT3 signaling pathways. 43 Rh4 also mitigates inflammation and oxidative stress by blocking the mitogen-activated protein kinase/nuclear factor κB (MAPK/NF-κB) signaling pathways. 44 Besides, Rh4 can activate the Wnt signaling pathway.…”
Section: ■ Discussionmentioning
confidence: 99%
“…IF staining of AT8 (Ser202 and Thr205) and AT180 (Thr231) showed that Rh4 significantly depressed the level of tau hyperphosphorylation. Actually, Rh4 can exert anti-inflammatory effects by regulating the NF-κB and STAT3 signaling pathways . Rh4 also mitigates inflammation and oxidative stress by blocking the mitogen-activated protein kinase/nuclear factor κB (MAPK/NF-κB) signaling pathways .…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of inflammation can lead to a variety of key diseases that constitute a major cause of death [ 4 , 5 ] and more than half of all deaths can be attributed to infection and inflammation-related diseases such as cancer, respiratory infections, diarrheal diseases, and cardiovascular diseases [ 6 ]. Traditional Chinese medicines were reported to share a broad antibacterial spectrum and low resistance, making them ideal drugs for anti-inflammatory treatment, and have been proven in previous studies [ 3 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%